31.3k views
3 votes
Help pleaseeeeeeeee.

Help pleaseeeeeeeee.-example-1

1 Answer

4 votes

Answer:

a) y*x = k

b) y = 3

Explanation:

a) According to given condition:

As in inverse relation, if one quantity increases other decreases proportionally so the equation will be:

y∝ 1/x

Now removing proportional sign with equality a constant k is used as follows:

y = k/x

k = y*x

Putting values of y and x, we get:

k = (7) * (9)=63

b) By putting given value of x in (k=y*x)

63 = y * (21)

y = 63/21

y = 3

User Pwmusic
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.